Profile of High School Students’ Sustainability Awareness in Chemistry Learning - Sari, Diah Kartika; Fethya, Revnika; Sofia, Sofia; Ad’hiya, Eka; Haryani, Maefa Eka; Sanjaya, Sanjaya (IJIS Edu : Indonesian Journal of Integrated Science Education, 2026)
This study aims to characterize students’ sustainability awareness in the context of chemistry learning at SMA Negeri 1 Indralaya Utara and to provide a basis for developing worksheets aligned with the Sustainable Development Goals (SDGs). A quantitative descriptive design was employed with a sample of 34 grade XII students selected through simple random sampling. The research instrument was a 36-item sustainability awareness questionnaire adapted from Kelfina et al. (2025), encompassing three dimensions: behavioral and attitudinal awareness, emotional awareness, and awareness of sustainability practices. Data were analyzed using mean scores and percentage distributions. The results show that students’ sustainability awareness was generally high, with an overall mean score of 82.33%. Each dimension also demonstrated high levels of awareness: 82.67% for behavioral and attitudinal awareness, 82.67% for emotional awareness, and 81.67% for awareness of sustainability practices. These findings suggest that chemistry learning particularly topics such as corrosion, green chemistry, and chemical bonding supports the development of students’ conceptual understanding, emotional engagement, and sustainable practices in daily life. Overall, the study provides an empirical foundation for developing chemistry worksheets integrated with the SDGs to further strengthen students’ sustainability awareness